UJI TOKSISITAS EKSTRAK ETANOL 96% DAUN MIANA (Plectranthus scutellaroides R.Br) TERHADAP Artemia salina DENGAN METODE BSLT (Brine Shrimp Lethality Test) - Puspita Sari, Dyah Ratna Ayu; Putu Yudha Ugrasena; Ni Putu Ayu Desi Astini; I Gede Agus Sindhu A (Journal Pharmactive, 2023)
Medicinal plants are one of the efforts used to control disease. The benefits of medicinal plants have been passed down from generation to generation by our ancestors. One plant that has medicinal properties is miana leaves (Plectranthus scutellaroides R.Br). In this research, the extraction method used was maceration, with 96% ethanol solvent. Miana leaf ethanol extract was screened for phytochemicals and toxicity tested using the Brine Shrimp Lethality Test (BSLT) method. Toxicity tests were carried out at various concentrations of 100 ppm, 250 ppm, 500 ppm, 750 ppm and 1000 ppm. The results of phytochemical screening on miana leaves show that miana leaves contain flavonoid compounds, tannins, saponins, steroids, but do not contain alkaloids and triterpenoids. The 96% ethanol extract of miana leaves (Plectranthus scutellaroides R.Br) has an LC50 value of 511.58 ppm, included in the toxic category with an LC50 value in the range of 30-1000 ppm.